Engineering Er-doped ZnO nanocrystals for As-removal: Targeting water remediation - Aragón, F. F.H.; Villegas-Lelovsky, L. [UNESP]; Parizaka, J. G.; Zela, E. G.; Bendezu, R.; Gallegos, R. O.; Coaquira, J. A.H.; Pacheco-Salazar, D. G.; da Silva, S. W.; Garnier, J.; Morais, P. C. (Elsevier, 2024)
Erbium-doped zinc oxide nanocrystals (Zn1−xErxO) produced by the polymeric precursor method are the subject of a comprehensive study in this report. Our results indicate that only the wurtzite ZnO phase is produced up to x = 0.050. After that (x > 0.050), a mixed system with a secondary phase (Er2O3) is found. The lower solubility limit of erbium in the ZnO crystal lattice is correlated with the higher ionic radii of Er3+-ions compared to Zn2+-ions, impacting remarkably the solid solution limit. Magnetic measurements show the coexistence of the two phases: paramagnetism (PM) related to Zn1−xErxO nanocrystals (free and short-range coupled Er3+-ions) and a weak ferromagnetic (FM) contribution assigned to the presence of bound magnetic polarons. UV–vis spectra show a transition from one to two excitonic peaks as the Er-content increases; the second peak related to the nucleation process of the secondary Er2O3 phase, which was successfully acknowledged using the Elliott's model. Fourier transform infrared (FTIR) spectroscopy was used to characterize vibrational properties and the results are in agreement with the x-ray diffraction data analysis. To assess the efficiency of using the Zn1−xErxO samples to remove As(V) from contaminated water, a reference water solution containing 500 ppb As(V), at a neutral (pH = 7), was prepared to simulate drinking water. Our results show the effectiveness of As-removal. It was determined that the effectiveness is improved with the Er-content, reaching the limit imposed by World Health Organization. According to the linearity achieved while applying the pseudo-second-order-adsorption model, our findings strongly suggest that a chemisorption mechanism takes place between the Zn1−xErxO nanoparticle surface and As(V) in solution.
Keywords: As-removal; Er-doped ZnO nanocrystals; Magnetic nanocrystals; Magnetic properties; Solid solution